Reasoning web semantic technologies for the web of data : 7th international summer school 2011, Galway, Ireland, August 23-27, 2011 : tutorial lectures - Summer School on Reasoning Web 2011 Galway, Ireland); Polleres, Axel.; SpringerLink (Online service). (Heidelberg Springer, 2011)
The Semantic Web aims at enriching the existing Web with meta-data and processing methods so as to provide web-based systems with advanced capabilities, in particular with context awareness and decision support. The objective of this book is to provide a coherent introduction to semantic web methods and research issues with a particular emphasis on reasoning. The 2011 school programme focused around the central topic of applications of reasoning for the emerging Web of Data with twelve exciting lectures. The chapters in the present book provide educational material and references for further reading. The excellent overview articles provided by the lecturers not only serve as accompanying material for the students of the summer school itself: we are happy to present a volume that also provides the general reader an entry point to various topics related to reasoning over web data.
Introduction to Linked Data and its Lifecycle on the Web -- Foundations of Description Logics -- Using SPARQL with RDFS and OWL Entailment -- Database foundations for scalable RDF processing.-Scalable OWL 2 Reasoning for Linked Data -- Rules and Logic Programming for the Web -- OWL and Rules -- Modeling the Web of Data -- Trust management methodologies for the Web -- Application and Evaluation of Inductive Reasoning Methods for the Semantic Web and Software Analysis -- Probabilistic-Logical Web Data Integration -- An Introduction to Constraint Programming and Combinatorial Optimisation. Foundations of Description Logics -- Using SPARQL with RDFS and OWL Entailment -- Database foundations for scalable RDF processing -- Scalable OWL 2 Reasoning for Linked Data -- Rules and Logic Programming for the Web -- OWL and Rules -- Modeling the Web of Data -- Trust management methodologies for the Web -- Application and Evaluation of Inductive Reasoning Methods for the Semantic Web and Software Analysis -- Probabilistic-Logical Web Data Integration -- An Introduction to Constraint Programming and Combinatorial Optimisation.
Electronic reproduction.
Keywords: Query languages (Computer science) -- Congresses; Semantic Web -- Congresses; Ontology -- Congresses; Knowledge representation (Information theory) -- Congresses; Electronic books